Small town girl [large type] : a novel - Gabhart, Ann H., 1947- (Center Point Large Print, 2013)
Kate Merritt worries love's passing her by until Jay Tanner shows up to charm her hesistant heart. Pearl Harbor changes everything, including Kate's chance for love.